Characterization of various fly ashes for preparation of geopolymers with advanced applications - Temuujin, J.; Rickard, William; Van Riessen, Arie (Elsevier, 2013)
Fly ashes from different power stations in Australia (Collie, Eraring, Tarong) and Mongolia (4th thermal power station, Ulaanbaatar city) have been characterized by various techniques. It was determined that the Australian fly ashes are class F while the Mongolian fly ashes are class C. Due to their chemical and mineralogical differences, the fly ashes behaved differently when alkali activated to make geopolymers. The influence of various parameters on the preparation of geopolymers have been investigated and the results are used to establish a procedure for the routine manufacture of alkaline activated products. The applicability of using fly ash for building structural elements, corrosion resistant and thermally resistant materials will be presented.